2011
DOI: 10.2478/s11686-011-0024-z
|View full text |Cite
|
Sign up to set email alerts
|

Philometra chilensis (Nematoda, Philometridae) affects the fecundity of the red cusk-eel, Genypterus chilensis (Guichenot) (Pisces, Ophidiidae) in Chile

Abstract: The occurrence of the dracunculoid nematode Philometra chilensis Moravec, Chávez et Oliva, 2011 (Philometridae) infecting the ovary of the red cusk-eel, Genypterus chilensis (Guichenot), off the Pacific coast of northern Chile is reported. A sample of 266 fish specimens (total body length 34-96 cm) revealed the nematode overall prevalence (April 2007) of this parasite to be 18.5% and the mean intensity of infection 17.9 (SD = 30.8). All infected fish were mature females. The present results suggest that infec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 12 publications
(11 reference statements)
1
12
0
Order By: Relevance
“…females of P. lateolabracis [up to 230 mm] can be markedly shorter than those of P. floridensis [up to about 1000 mm]; Moravec 2006, Moravec et al 2010). Our intensity measurements were similar to those of Hesp et al (2002; a maximum of 7 nematodes per host) and in contrast to those of Moravec et al (1997), Clarke et al (2006), and Chávez & Oliva (2011) who reported extreme intensities of 84, >100, and 99 nematodes per host in Epinephelus morio infected by P. margolisi, Pomatomus saltatrix infected by Philometra saltatrix and Genypterus chilensis infected by P. genipteri (reported as P. chilensis), respectively. In these latter cases, intense infections were associated with substantial concurrent pathological changes.…”
Section: Prevalence and Intensitysupporting
confidence: 86%
See 1 more Smart Citation
“…females of P. lateolabracis [up to 230 mm] can be markedly shorter than those of P. floridensis [up to about 1000 mm]; Moravec 2006, Moravec et al 2010). Our intensity measurements were similar to those of Hesp et al (2002; a maximum of 7 nematodes per host) and in contrast to those of Moravec et al (1997), Clarke et al (2006), and Chávez & Oliva (2011) who reported extreme intensities of 84, >100, and 99 nematodes per host in Epinephelus morio infected by P. margolisi, Pomatomus saltatrix infected by Philometra saltatrix and Genypterus chilensis infected by P. genipteri (reported as P. chilensis), respectively. In these latter cases, intense infections were associated with substantial concurrent pathological changes.…”
Section: Prevalence and Intensitysupporting
confidence: 86%
“…Gonad-infecting parasitic nematodes of the family Philometridae have been reported to cause significant damage to the gonads of wild and cultured marine perciform hosts with varying consequences including severe reduction in reproductive fitness based on gross and histological pathology (Rama chandran 1975, Hine & Anderson 1981, Sakaguchi et al 1987, Oliva et al 1992, Hesp et al 2002, Clarke et al 2006, Moravec 2006, Perez et al 2009, Chávez & Oliva 2011. Reports of reproductive effects utilizing direct quantifiable measures acceptable to fisheries biologists are generally wanting for this group , and there is no specific information on health or reproductive effects of Philometra floriThe red drum is an economically important sport and food fish, and is the only reported host for the ovarian parasite Philometra floridensis.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, a higher prevalence of Philometra sp. in the ovary than in the testes was found in Paralichthys adspersus , Glaucosoma ebraicum , Cynoscion nebulosus , Genypterus chilensis and Sciaenops ocellatus (Oliva et al., ; Hesp et al., ; Perez et al., ; Chávez and Oliva, ; Bakenhaster et al., ). Philometrids often affect only one gender of a given species (Moravec and de Buron, ); similarly in this case, no male gonads of P. erythrinus were parasitized.…”
Section: Discussionmentioning
confidence: 98%
“…New data concerning these patterns are mentioned above (Perez et al 2009, chávez and oliva 2011, seguin et al 2011, Williams et al 2012. However, despite the fact that life history data are lacking for the great majority of philometrid species, too little attention (only three papers) has been paid to the life cycles of these nematode parasites in the recent years and few studies have been initiated to address this problem.…”
Section: Studies On Philometrid Life Cyclesmentioning
confidence: 99%
“…In several fish species, the presence of philometrids in host ovaries seems to occur in fish that have reached maturity (Hesp et al 2002, Perez et al 2009, radhakrishnan et al 2010, chávez and oliva 2011, and it has been suggested that immature fish are not susceptible to infection (chávez and oliva 2011) or that there might be a synchrony between host and parasite maturation (Perez et al 2009). the presence of philometrids in host gonads has been suggested by numerous authors to negatively affect the reproduction of some species of marine fishes (Hine and Anderson 1981, sakaguchi et al 1987, Moravec and salgado-Maldonado 2007, Moravec et al 2007a) and recent studies (see below) generally support this contention.…”
Section: A H D C B E G Fmentioning
confidence: 99%